Methylprednisolone Vs Dexamethasone in Treating Patients with Covid-19 - Bushra Shaheen, Saira Mushtaq, Waqas Qarshi, Sajjad Ghani, Zarrin Khaliq Chaudari, Hafiz Muhammad Imran Aziz (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To compare the efficacy of intravenous dexamethasone and methylprednisolone on the treatment of hospitalized patients with covid-19. Methods: Between January 2022 and September 2022, 46 COVID-19 positive patients from the medical ward of ABWA Hospital and Research Centre participated in a randomized controlled trial. Patients in group A were given dexamethasone, whereas those in group B were given methylprednisolone. Hyperglycemia, hypokalemia, duration of oxygen therapy, death, intensive care unit hospitalization, and other outcomes were measured in both groups. For qualitative variables, Chi Square test was used, while for quantitative variables, T-Test was used. A significance level of less than 0.05 was used. Results: In Group A, the average duration of hospitalization was 7.13±2.26days, but in Group B, it was 9.61±2.33 days (P = 0.0001). Group A had considerably shorter O2 therapy duration than Group B (5.78±1.16 days vs. 8.48±1.90 days; P = 0.0001). Group A had a considerably reduced incidence of hyperglycemia and hypokalemia compared to Group B (34.8% vs 73.9%, P = 0.008) (13% vs 43.5, P = 0.02). Conclusion: We conclude that 8mg/day dexamethasone is better than 30mg methylprednisolone twice a day in treatment of COVID-19. Keywords: Efficacy, Covid-19, Dexamethasone, Methylprednisolone